Sie sind auf Seite 1von 2

Proofs of Parsevals Theorem & the Convolution Theorem

(using the integral representation of the -function)


1 The generalization of Parsevals theorem
The result is
_

f(t)g(t)

dt =
1
2
_

f()g()

d (1)
This has many names but is often called Plancherels formula.
The key step in the proof of this is the use of the integral representation of the -function
() =
1
2
_

e
i
d or () =
1
2
_

e
i
d . (2)
We frstly invoke the inverse Fourier transform
f(t) =
1
2
_

f()e
it
d (3)
and then use this to re-write the LHS of (1) as
_

f(t)g(t)

dt =
_

_
1
2
_

f()e
it
d
__
1
2
_

g(

e
i

t
d

_
dt . (4)
Re-arranging the order of integration we obtain
_

f(t)f(t)

dt =
_
1
2
_
2
_

f()g(

__

e
i(

)t
dt
_
. .
Use deltafn here
d

d . (5)
The version of the integral representation of the -function we use in (2) above is
(

) =
1
2
_

e
it(

)
dt . (6)
Using this in (5), we obtain
_

f(t)g(t)

dt =
1
2
_

f()
__

g(

) d

_
d
=
1
2
_

f()g()

d . (7)
(7) comes about because of the general -function property
_

F(

)(

) d

= F().
2 Parsevals theorem (also known as the energy theorem)
Taking g = f in (1) we immediately obtain
_

|f(t)|
2
dt =
1
2
_

|f()|
2
d . (8)
The LHS side is energy in temporal space while the RHS is energy in spectral space.
Example: Sheet 6 Q6 asks you to use Parsevals Theorem to prove that
_

dt
(1+t
2
)
2
= /2.
The integral can be evaluated by the Residue Theorem but to use Parsevals Theorem you will
need to evaluate f() =
_

e
it
dt
1+t
2
. To fnd this, construct the complex integral
_
C
e
iz
dz
1+z
2
and
take the semi-circle C in the upper (lower) half-plane when < 0 (> 0). The answers are e

when < 0 and e

when > 0. Then evaluate the RHS of (8) in its two parts.
1
3 The Convolution theorem and the auto-correlation function
The statement of the Convolution theorem is this: for two functions f(t) and g(t) with Fourier
transforms F[f(t)] = f() and F[g(t)] = g(), with convolution integral defned by
1
f g =
_

f(u)g(t u) du, (10)


then the Fourier transform of this convolution is given by
F (f g) = f() g() . (11)
To prove (11) we write it as
F (f g) =
_

e
it
__

f(u)g(t u) du
_
dt . (12)
Now defne = t u and divide the order of integration to fnd
F (f g) =
_

e
iu
f(u) du
_

e
i
g() d = f() g() . (13)
This step is allowable because the region of integration in the u plane is infnite. As we shall
later, with Laplace transforms this is not the case and requires more care.
The normalised auto-correlation function is related to this and is given by
(t) =
_

f(u)f

(t u) du
_

|f(u)|
2
du
. (14)
1
It makes no diference which way round the f and the g inside the integral are placed: thus we could write
f g =
_

f(t u)g(u) du. (9)


2